Three maps by Father Samuel Fritz of the Peruvian Amazon basin (17th century) seen through the eyes of a linguist - Solís Fonseca, Gustavo (2011)
This is a study about the languages and peoples of the Amazon in the late seventeenth century, departing from three maps elaborated by the missionary Samuel Fritz. The aim of the article is to provide a linguistic perspective on the Amazonian peoples and languages at that time period, in order to provide a delineation of the spaces that these languages once occupied, as well as of the ones that the surviving languages occupy today. The three maps made by Father Fritz allow us to identify languages and peoples, linked to certain geographical areas in the Amazon at that time period, and they also reveal numerous cases of extinction of peoples and their respective linguistic creations.